Organic soil amendments and food security: Evidence from Cameroon - Tabe-Ojong, Martin Paul Jr.; Fabinin, Akem Nina; Nzie, Jules Rene Minkoua; Molua, Ernest Lytia; Fonkeng, Eltson Eteckji (Wiley, 2023)
Food insecurity remains a persistent policy issue in many developing countries. While socio-political, epidemiological, climatic, and productivity-related factors have received attention regarding food insecurity, a rarely considered factor is the changing quality of the soil, a natural resource base that has the potential of increasing or reducing vulnerability to food insecurity. The use of organic soil amendments may be socioeconomically and environmentally advantageous. This study examines the inherent relationship between the use of organic soil amendments and food security among smallholder farming households. Using the seemingly unrelated bivariate probit model and the recursive bivariate probit model on nationally representative household-level data from Cameroon, we find evidence that the use of organic soil amendments is positively associated with household food security. We also find the use of organic soil amendments to be associated with reduced levels of mild, moderate, and severe food insecurity. Empirical evidence is also suggestive of a positive association between crop diversification and food security. The results further show that households with larger farm sizes tend to use more organic soil amendments than households with smaller farms. Taken together, our findings confirm another pathway of improving food security with implications for the broad path towards achieving the Sustainable Development Goals (SDGs), particularly SDG 2 of ending hunger.